BASES OF DEVELOPMENT OF METHODS OF ADJUSTING OF OFFICE HOURS OF THE DIFFICULT GAS-TRANSPORT SYSTEMS - Тимків, Дмитро Федорович; Онацко, Роман Георгійович; Михалевич, Олег Тадейович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The model of the gas-transport system intended for the analysis of gas streams and process control of transporting of gas is built.